2005
DOI: 10.1007/s10509-005-4321-6
|View full text |Cite
|
Sign up to set email alerts
|

A Cosmological Explanation to the Pioneer Anomaly

Abstract: An earlier paper introduced a new cosmological theory based on the proposition that all four metrical coefficients of space and time change with the cosmological expansion. Such a universal scale expansion would preserve the four-dimensional spacetime geometry and therefore by general relativity most physical relationships. In addition, if the scale expansion were exponential with time, all epochs would be equivalent. The theory resolves several outstanding problems with the standard model based on the Big Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It turns out that at low luminosities there is very poor agreement with the SCM theory's number-count prediction, while the SEC theory agrees excellently with the observations (Masreliez 1999(Masreliez , 2004a(Masreliez , 2006c. Figure 2 shows a summary from 16 different number-count programs taken from a paper by Metcalf et al (1995).…”
Section: The Number-count Testmentioning
confidence: 64%
See 2 more Smart Citations
“…It turns out that at low luminosities there is very poor agreement with the SCM theory's number-count prediction, while the SEC theory agrees excellently with the observations (Masreliez 1999(Masreliez , 2004a(Masreliez , 2006c. Figure 2 shows a summary from 16 different number-count programs taken from a paper by Metcalf et al (1995).…”
Section: The Number-count Testmentioning
confidence: 64%
“…The author has investigated this possibility in a series of papers that introduce and explore the scale expanding cosmos (SEC) model and has found that it describes our universe as observed (Masreliez 1999(Masreliez , 2004a(Masreliez , 2006c. The SEC model better agrees with observational data than the standard cosmological model (SCM) based on the Big Bang theory.…”
Section: This Is 4d Scale-equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…But indirect identifications could be fruitful: for instance, the expansion coefficient could be deduced from (26), the mass repartition parameters can be deduced from close observations of such curves as shown fig.1, etc. More simply, close observation of plain "linear" movement of "free" spacecrafts (Masreliez, 2005;Minguzzi, 2006;Nottale, 2003) could be of particular interest to verify such accelerations as stated by (4) or (30).…”
Section: Conclusion and Commentsmentioning
confidence: 95%
“…1, etc. More simply, close observation of plain "linear" movement of "free" spacecrafts (Masreliez, 2005;Minguzzi, 2006;Nottale, 2003) could be of particular interest to verify such accelerations as stated by ( 4) or (30).…”
Section: Conclusion and Commentsmentioning
confidence: 95%